Pengaruh Penerapan Safety Risk Management terhadap Pelayanan Lalu Lintas Penerbangan di Approach Control Unit Perum LPPNPI Cabang Denpasar - Dwi Lestary; Bagus Prakoso; Pangsa Rizkina Aswia; Dhiayu Handayantri (Politeknik Penerbangan Makassar, 2023)
This study aims to see how much the influence of Safety Risk Management Implementation has on air traffic services at the Approach Control Unit of Perum LPPNPI Denpasar Branch by using quantitative methods. The sample in this study were all ATC personnel at the Approach Control Unit of Perum LPPNPI Denpasar Branch. Data is collected using a questionnaire, which is then processed through validity, reliability, normality, linearity, and associative hypothesis testing with correlation, significance, determination, and simple linear regression tests. The results showed that there was a strong influence, with a correlation of 0.719 and a coefficient of determination of 51.8%, and the rest was influenced by other factors. With the linear regression equation Y = 20.405 + 0.683X + e, if Safety Risk Management (X) increases by one unit, then Air Traffic Services (Y) will increase by 0.683 units.